The planning evaluation of competences in higher education - Mari Paz García Sanz; Laura Raquel Morillas Pedreño (Revista Electrónica Interuniversitaria de Formación del Profesorado)
The presentations defended by the European Higher Education Area (EHEA) imply an individual and combined reflection with regard to the three fundamental and interrelated tasks of the educational involvement: the planning, the execution of the education and the evaluation. In this article we are going to centre on some aspects of the first of these tasks: the educational planning. Specifically we are focusing the study on the formulation of competence and on the evaluation of these as elements to include in the educational guides of the university subjects of Degree and Post degree. The work is framed in a competencial model, in that, as its name suggests, the center of the process of education-learning is the competence that the student has to reach, therefore the rest of the elements of the curriculum depend on the above mentioned competence. One of these elements is the evaluation, therefore it has to be orientated to demonstrate the acquisition of competence and to improve the quality and the quantity of the educational processes.